La fauna de Coleoptera Melolonthidae de la Reserva de la Biósfera El Triunfo, Chiapas, México - Morón Ríos, Alejandro; Morón, Miguel Ángel (Instituto de Ecología, A.C., 2001)
A study on the species of Melolonthidae was conducted in the Biosphere Reserve El Triunfo, located in the southeastern portion of Sierra Madre del Sur, Chiapas state, Mexico. Collections were made using a light trap, rotting fruit traps, and direct capture on plants, between 1997 and 1998. Fourty species were collected, from 24 genera of Melolonthinae, Rutelinae, Dynastinae, Cetoniinae and Trichiinae. Phyllophaga, Anomala and Cyclocephala had the greatest number of species. Species recently described in the genera Yaaxkumikia, Anomala, Mesosternus, Parisoleoides, Chrysina, Plusiotis, Hologymnetis and Phyllophaga, are recorded. Hoplia subcostata Bates and Plusiotis quiche Morón are recorded for the first time in Mexico; and the record of Archedinus relictus Morón and Krikken, as relictual species is confirmed. Based on the species accumulation per collection effort, it is estimated that the present collection accounts for 70% of the nocturnal species of Melolonthidae in the reserve. A preliminary key to the species from the Biosphere Reserve is included.